Setting standards and monitoring quality in the NHS 1999–2013: a classic case of goal conflict. (19th July 2016) - Littlejohns, Peter; Knight, Alec; Littlejohns, Anna; Poole, Tara‐Lynn; Kieslich, Katharina
Abstract: 2013 saw the National Health Service (NHS) in England severely criticized for providing poor quality despite successive governments in the previous 15 years, establishing a range of new institutions to improve NHS quality. This study seeks to understand the contributions of political and organizational influences in enabling the NHS to deliver high‐quality care through exploring the experiences of two of the major new organizations established to set standards and monitor NHS quality. We used a mixed method approach: first a cross‐sectional, in‐depth qualitative interview study and then the application of principal agent modeling (Waterman and Meier broader framework). Ten themes were identified as influencing the functioning of the NHS regulatory institutions: socio‐political environment; governance and accountability; external relationships; clarity of purpose; organizational reputation; leadership and management; organizational stability; resources; organizational methods; and organizational performance. The organizations could be easily mapped onto the framework, and their transience between the different states could be monitored. We concluded that differing policy objectives for NHS quality monitoring resulted in central involvement and organizational change. This had a disruptive effect on the ability of the NHS to monitor quality. Constant professional leadership, both clinical and managerial, and basing decisions on best evidence, both technical and organizational, helped one institution to deliver on its remit, even within a changing political/policy environment. Application of the Waterman–Meier framework enabled an understanding and description of the dynamic relationship between central government and organizations in the NHS and may predict when tensions will arise in the future. © 2016 The Authors. The International Journal of Health Planning and Management Published by John Wiley & Sons Ltd.